The ampulla of Vater: A potential target for metastatic melanoma?. Issue 1 (18th January 2023) - Armany, David; Gosal, Preet; Adams, Stuart
Abstract: Malignant melanomas are aggressive cancers that can prove to be fatal, with Australia harbouring the highest incidence of skin cancers worldwide. Surprisingly, as little as 13.4% of patients undergoing surgical resection of high-risk melanomas remain disease-free after 2 years, with 31.6% showing evidence of distant spread. Although rare, secondary tumours of the ampulla of Vater have been documented, with the most common primaries involving breast, renal and melanoma cancers. We report the case of a malignant melanoma of the ampulla of Vater occurring in a patient 4-year post-surgical resection of a Stage II melanoma manifesting as acute pancreatitis with obstructive jaundice. Given the rarity of secondary ampullary tumours, metastatic melanoma should always be considered in patients with obstructive jaundice and a history of melanoma resection. In the absence of distant disease, surgery may be considered after consensus at multidisciplinary team meetings and after consideration of the patient preference.